Exploring of Hegemony in the Novel the Kite Runner, A Thousand Splendid Suns, Girl of Kosova, and The Thief of Baghdad - Siti Nabila Amira Wangsi; Tri Ramadani; Zahra Tinaendah Mayanti; Nurholis Nurholis (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research explores the depiction of hegemony in four literary works: The Kite Runner and A Thousand Splendid Suns by Khaled Hosseini, Girl of Kosovo by Alice Mead, and The Thief of Baghdad by Alexander Romanoff. Through Antonio Gramsci's theory of hegemony, this research analyzes the impact of political, ethnic and patriarchal power on individuals and society. In The Kite Runner, ethnic hierarchy in Afghanistan is reflected through Pashtun-Hazara relations. A Thousand Splendid Suns reveals the oppression of patriarchy and the Taliban regime's rule over women. In contrast, Girl of Kosovo depicts the trauma of war through political-military domination amidst ethnic conflict in the Balkans. The Thief of Baghdad presents a fantasy narrative of resistance to the tyranny of the authorities through symbolism and class tensions. Although set in different contexts, these four works demonstrate the universal theme of struggle against hegemonic power and the role of literature in articulating both trauma and hope. The analysis uses a qualitative approach by examining quotations, symbolism, dialogue, and characterization to identify forms of hegemony. As a result, literature becomes a reflective medium that highlights the multidimensional impact of hegemony in history and culture. This research demonstrates the relevance of Gramsci's theory in understanding complex global socio-political dynamics.